STATISTIC FOR ENGINEERING STUDENTS - DAVID DANIEL , BASIL (Penerbit UTHM, 2024)
Engineers have long valued statistics because they may apply them to understand the data gathered from field work, experiments, testing, assessments, research and other operations. Numerous aspects of engineering largely rely on statistics, including the use of statistical models for problem-solving and making predictions, statistical tests for testing hypotheses, and probability-based decision-making. Statistics For Engineering Students was specifically written with pre-university and university students in mind, and with the aim of providing a better understanding on statistics and how it may be used in the engineering world. This book explores common statistical tests and analysis that are presented in the simplest manner as possible to aid students’ comprehension of the topics covered, particularly descriptive and inferential statistics. Examples and exercises dealing with parametric and non-parametric tests have been included in this book as well. This is not only to ensure students thoroughly understand the need for conducting statistical analysis, but are able to relate statistics with engineering, and apply them if required in their respective job scopes when they embark on a career in the engineering industry.